Evaluation of coffee husk for milk production in cows - Geevarghese P I (Department of Dairy Science, College of Veterinary and Animal Sciences, 1979)
An investigation was carried out to find out the feeding value of coffee husk for milk production in cows using a total of nine Sindhi x Jersey cross bred cows, divided into three groups of three animals each. The experiment was for a period of 90 days. Coffee husk was included in the concentrate mixture at 0, 10 and 20 per cent levels. A switch – over design was used for the experiment. Coffee husk fed at 10 and 20 per cent levels in the concentrate ration did not significantly influence the body weight of animals. The total milk production of the animals getting coffee husk in the ration did not significantly differ from that of the animals on the control diet. The percentage of fat in milk, the total quantity of milk fat produced, the amount of four per cent fat – corrected milk, the percentage of total solids, the amount of total solids in milk, percentage of solids – not –fat, total quantity of solids – not – fat and the amount of solids – corrected milk remained the same for all the three groups of animals included for the study and no significant differences were noticed due to treatments. The physiological status of the cows in all the groups was normal and satisfactory. No significant difference due to treatments was noticed in some of the physical and chemical constants of butter fat. The dairy merit (percentage) based on efficiency of feed conversion was less of animals getting ten per cent coffee husk due to the reduced milk production and the greater feed consumption. The total cost of feed for producing one kg milk was Rs.1.42, 1.38 and 1.33 for animals getting 0, 10 and 20 per cent coffee husk in the concentrate mixture respectively. It was concluded that coffee husk upto 20 per cent level can profitably be incorporated in the concentrate mixture of dairy cows.